Loisir et inclusion : l'expérience inclusive de loisir au service d'une société solidaire - Carbonneau, Hélène; Reichhart, Frédéric (Loisir et société, 2025)
Leisure activities are an avenue for developing a sense of belonging insofar as recreation contexts are conducive to enabling an inclusive experience. Achieving an inclusive leisure experience implies access to spaces and equipment that enable meaningful leisure practice, mobilizing the person's potential and enabling him or her to relate satisfactorily to others. Inclusion seen from this angle concerns not only people with disabilities, but anyone who may face marginalization because of their differences. This conceptual article calls for further reflection on the conditions and scope of the inclusive leisure experience